Awareness of breast cancer risk factors and practice of breast self - examination among female students in Medical Faculty, Udayana University, Bali - Shalini Kalithasan; Gede Eka Rusdi Antara (Intisari Sains Medis, 2019)
Background: Breast cancer patients generally have low rates of survival rates due to late-stage diagnosis as patients usually present at and late stage because of lack of awareness and ignorance of risk factors.Methods: The objectives of this study are to evaluate the knowledge of risk factor for breast cancers and the practice of breast self-examination among female students in medical faculty at Udayana University. A cross sectional study conducted over a period of one month. 100 female students were volunteered to take part in the survey. The data were analyzed descriptively.Results: A half of the students have moderate knowledge of breast cancer risk factors, and the majority of the students do not practice breast self-examination monthly.Conclusions: It was suggested to students have more concern about relevant education programs that are having around them.Â